2016
DOI: 10.4103/0970-4388.191430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of newer antioxidants on the bond strength of composite on bleached enamel

Abstract: It can be concluded that the use of antioxidant before bonding procedures on bleached enamel completely neutralizes the deleterious effects of bleaching and increases the bond strength significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 0 publications
4
24
0
Order By: Relevance
“…On comparison of group C with group F significantly higher shear bond strength for Proanthocyanidin was seen. The results were in agreement with previous studies done by Manoharan et al 1 and Vidhya et al 2 this can be due to three reasons that are: • specificity of proanthocyanidin for hydroxyl free radicals. 20 • The superoxide radicals being trapped by the multiple donor sites found on oligomeric proanthocyanidin (OPC).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On comparison of group C with group F significantly higher shear bond strength for Proanthocyanidin was seen. The results were in agreement with previous studies done by Manoharan et al 1 and Vidhya et al 2 this can be due to three reasons that are: • specificity of proanthocyanidin for hydroxyl free radicals. 20 • The superoxide radicals being trapped by the multiple donor sites found on oligomeric proanthocyanidin (OPC).…”
Section: Discussionsupporting
confidence: 93%
“…8 • The free radical scavenging activity enhanced by the esterification of epicatechin by gallic acid in OPCs. 1 Arumugam et al observed that Sodium ascorbate had a better potential in elevating the bond strength of enamel surface than proanthocyanidin. The probable reasons for disagreement are the different bleaching methodology used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique is clinically relevant and applicable for those patients that require restorative treatment immediately after in-office bleaching techniques [16]. Moreover, use of antioxidant (10% sodium ascorbate gel or 5% proanthocyanidin agent) before bonding procedures on bleached enamel neutralizes completely the deleterious effects of bleaching and significantly increases the bond strength [17].…”
Section: Additional Clinical Interventionsmentioning
confidence: 99%